Hypertension among youths—United States, 2001–2016. Issue 9 (30th August 2018) - Jackson, Sandra L.; Zhang, Zefeng; Wiltz, Jennifer L.; Loustalot, Fleetwood; Ritchey, Matthew D.; Goodman, Alyson B.; Yang, Quanhe
Abstract : This report reviews how the implementation of new definitions for hypertension in pediatric patients (a major risk factor for cardiovascular disease) has resulted in its increased prevalence, especially in youths with severe obesity.